Dentinal Tubule Occlusion Using Diode Laser and Nano-Hydroxyapatite: An In-vitro SEM Analysis - Salehpour, Samaneh; Rahmani, Marjan (Journal of Dental School, 2026)
Objective(s): This research aimed to evaluate the effect of diode laser and Remin Pro (containing nano-hydroxyapatite), both individually and in combination, on the occlusion of dentinal tubules. Methods: 45 extracted human premolar teeth were sectioned to create a 3×8 mm rectangle in the outer third of the cervical coronal dentin. The samples were then divided into five groups: negative control (with a smear layer), positive control (without a smear layer), diode laser (980 nm), Remin Pro, and combination of both. Dentinal tubule occlusion was evaluated using SEM at 2000x. Statistical analysis was performed using one-wayANOVA and LSD test at p<0.05. Results: The positive control exhibited the highest average percentage of open dentin tubules at 10.33%, while the combination treatment group showed the lowest percentage at 2.02%. When comparing the treatment methods to the positive control, all three treatments demonstrated statistically significant results (P = 0.000, 0.017, and 0.000). However, no significant statistical differences were found when the three treatment groups were compared to one another (P= 0.279, 0.935, and 0.733). Conclusion: All three treatment methods—Diode laser, Remin Pro, and their combination—effectively occluded dentinal tubules; however, none demonstrated superiority over the others.